Flyover Development Effectiveness In The Road Of Teuku Umar - Za Pagar Alam Bandar Lampung - Pradana, Ridho; Sulistyorini, Rahayu; Karami, Muhammad (Universitas Lampung, 2021)
Congestion problems are common in transportation, congestion can be caused by several things. The construction of the flyover is expected to be able to overcome congestion in the long term. This research was conducted to determine the effectiveness of the flyover construction on the Teuku Umar - ZA Pagar Alam road. This research was conducted during busy hours on Monday at the Teuku Umar road, ZA Pagar Alam and the nearest intersection.. From the results of calculations and analysis, it can be seen that the construction of an elevated bridge has no significant impact on the decomposition of the congestion problem in the Kedaton area and its surroundings, this can be seen from the level of service on all roads in the study area with a value of V / C Ratio <0.75. Meanwhile, the average degree of saturation obtained from the analysis of intersections with signal and no signal> 0.75. Construction of a flyover which illustrates that it will unravel traffic jams, in fact the performance of the flyover and the main road underneath has not increased. This needs to be addressed immediately considering the current traffic flow in Kedaton and its surroundings is already saturated. Therefore, the growth of vehicles is on time, and public transportation facilities need to be improved. So that people begin to switch to public transportation in order to reduce the incidence of congestion on these roads. Keywords : Road Performance, Degree of Saturation, Level of Road Service